Microbialitos da formação Codó (Aptiano Superior) às margens do rio Tocantins em São Miguel do Tocantins (TO) - Costa, Marry Delatorre [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The southwestern region of the São Luís-Grajaú Basin has a rare outcrop of the Codó Formation (upper Aptian) with seven outstanding microbialite bioherms along the left margin of the Tocantins river, near Imperatriz (MA). Resting on sandstones of the Grajaú Formation, the Codó Formation presents: 1) a 20 cm thick basal calcilutite with gypsite pseudomorphs and some fossil tree stems; 2) metric dark shales with carbonate nodules and thin intercalated carbonate layers, enclosing some microbial laminites; 3) a 2 cm thick upper breccia composed of microbialite fragments and other carbonate clasts, with halite hoppers on the top; 4) the carbonate bioherms, which partially overlie the extensive shales and interrupt them laterally, as well as the breccia. The bioherms in the northern part of the outcrop are thicker (<2 m) and have interbedded dark shales, whereas the southern are thinner and continuous in the vertical direction. In general, they are composed of irregular gently to strongly wavy microbial laminites, sometimes with pseudocolumnar to conical lamination. All microbialites with highest synoptic relief (<20 cm) look like columnar stromatolites on weathered lateral expositions. In plan view, the horizontal sections of these microbialites are circular to slightly elliptic, sometimes forming very small channels (N60W) filled with fine breccia. The highest bed of the northern bioherm has mixed microbial laminites and columnar stromatolites, where intercolumnar spaces were filled with microbialite clasts, fish bones, plant fragments and very small probable crustacean coprolites. Several fractures and deformation in this upper bed indicate an initial brecciation process probably caused by subaerial exposure. In microscopic scale, the lamination is smooth, diffuse, defined by subtle granulation differences of very fine granular calcite crystals within micrite, but oxide levels, dissolution surfaces or thin precipitated calcite veneers...

A região sudoeste da Bacia de São Luís-Grajaú possui um raro afloramento da Formação Codó (Aptiano superior) com sete espetaculares bioermas de microbialitos ao longo da margem esquerda do rio Tocantins, próximo a Imperatriz (MA). Sobrepondo arenitos da Formação Grajaú, a Formação Codó apresenta: 1) um calcilutito (20 cm de espessura) com pseudomorfos de gipsita e alguns caules fósseis; 2) folhelhos escuros métricos com nódulos calcários e intercalações de finas camadas de carbonato, incluindo alguns laminitos microbianos; 3) uma brecha superior (2 cm de espessura) composta por fragmentos de microbialitos e outros clastos carbonáticos, com hoppers de halita no topo; 4) os bioermas carbonáticos, os quais sobrepões parcialmente os extensos folhelhos e os interrompem lateralmente, assim como a brecha. Os bioermas na parte norte do afloramento são mais espessos (<2 m) e têm intercalações de folhelhos escuros, enquanto que os meridionais são mais delgados e são verticalmente contínuos. Em geral, são compostos por laminitos microbianos com lâminas irregulares, pouco a muito ondulados, às vezes com laminação pseudocolunar a cônica. Todos os microbialitos com o mais alto relevo sinóptico (<20 cm) têm aspecto de estromatólitos colunares nas superfícies intemperizadas. Em planta, as seções horizontais dos microbialitos são circulares a levemente alongados, às vezes definindo estreitos canais (N60W) preenchidos por fina brecha. A camada mais alta do bioerma setentrional apresenta microbialitos mistos de laminitos microbianos e estromatólitos colunares, onde espaços intercolunares estão preenchidos por clastos de microbialitos, pequenos ossos de peixes, fragmentos de plantas e prováveis pequenos coprólitos de crustáceos. Muitas fraturas e deformação nesta camada superior indicam início de um processo de brechamento provavelmente causado por exposição subaérea. Na escala microscópica, a laminação...
Keywords: Rochas; Carbonatos; Geologia estratigráfica - Cretáceo; São Miguel do Tocantins (TO); Tocantins, Rio (TO)